PENGARUH KINERJA INTELLECTUAL CAPITAL, LEVERAGE, DAN SIZE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Sari, Henny Mustika; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The globalization era has made business competition becomes more competitive, it forces the company to increasetheir innovation to the business management and competition strategy. Pharmaceutical and cosmetics sectormanufacturing companies are selected since this sector has a wide scope so many capitals are involved includingintellectual capital primarily in Human Capital, Structural Capital, and Customer Capital. This research ismeant to prove empirically the influence of VAIC, Leverage, and Size to the disclosure of intellectual capital. Theindependent variables which have been applied in this research is performance of intellectual capital which ismeasured by using Value Added Intellectual Coefficient (VAIC), size, and leverage method. The dependentvariable of this research is disclosure of intellectual capital (ICD). The analysis method has been carried out byusing panel data. Based on the result of the test which is the performance of intellectual capital (VAIC) does nothave any influence to the variable of intellectual capital. The leverage variable does not have any influence to thevariable of disclosure of intellectual capital. The Size variable has an influence to the variable of intellectualcapital.Keywords: Intellectual capital, Leverage, Size, Disclosure of Intellectual Capital.